Elucidation of microRNA miR-6744-5p regulation of anoikis in breast cancer cell lines and potential for therapeutic applications / Sharan Malagobadan - Sharan , Malagobadan (2019)
Anoikis is apoptosis induced when cells are detached from the extracellular matrix and neighbouring cells. Since anoikis serves as a regulatory barrier, cancer cells often acquire resistance towards anoikis during tumorigenesis to become metastatic. MicroRNAs (miRNAs) are short strand of RNA molecules regulating genes post-transcriptionally, by binding to mRNAs and reducing the expression of its target genes. This study aims to elucidate the role of a novel miRNA, miR-6744-5p, in regulating anoikis in breast cancer and identify its target gene. Anoikis resistant variant of luminal A type breast cancer MCF-7 cell line (MCF-7-AR) was generated by selecting and amplifying surviving cells after repeated exposure to growth in suspension. miRNA microarray revealed a list of dysregulated miRNAs, from which miR-6744-5p was chosen for overexpression and knockdown studies. In MCF-7, overexpression of miR-6744-5p increased anoikis as shown by viability and caspase-3/7 activity assay, inhibited cell migration as shown by wound healing assay and increased E-cadherin expression as shown by Western blotting. Knockdown of miR-6744-5p decreased anoikis, increased cell migration and decreased E-cadherin expression. In the invasive triple-negative breast cancer cell line MDA-MB-231, overexpression of miR-6744-5p promoted anoikis and inhibited cell migration but knockdown of miR-6744-5p produced no effect. Additionally, overexpression of miR-6744-5p also induced morphological changes of MDA-MB-231 cells and inhibited invasiveness of the cells in vitro in transwell invasion assay and in vivo in zebrafish larva metastasis model. Furthermore, N-acetyltransferase 1 (NAT1) has been identified and validated as the direct target of miR-6744-5p using luciferase reporter assay and western blot. Overall, this study has proven the ability of miR-6744-5p to increase anoikis in both luminal A and triple negative breast cancer cell lines, highlighting its therapeutic potential in treating breast cancer.